“I’m not that kind of Malay" : negotiating Malay identity in Singapore - Sanwari, Farah Nurdiyanah (2016)
This paper seeks to explore the construction of Malay ethnic identity against the backdrop of the disparaging public discourse and stereotypes surrounding Malays. Drawing on interactionist paradigm, I engage with the theory of ‘Othering’ in uncovering the process of identity formation. I conducted in-depth semi-structured interviews with 14 Malay youths from a range of socio- economic and educational background. The data revealed that 1) everyday racism and the public discourse on Malays largely shape Malays’ negative perception of themselves and their ethnicity; 2) the extent of internalized racism is felt differently across social class, where the educated middle class are most likely to experience class anxiety; 3) respondents adopt strategies (defensive othering, social distancing, and language use) as an adaptive response, reinforcing ingroup discrimination; 4) Malays’ policing of piety and gender reinforce pressures faced within the Malays. This study contributes to the larger study on identity work among Singaporean Malays, proving a ground-level analysis of Malay identity. The results reveal the need for Malays to have a more critical outlook on public discourse on Singaporean Malays and for a more reflexive attitude towards understanding other Malays.